Working memory, metacognition and foreign language reading comprehension: a bibliographical review - Woelfer, Sidnei Werner; Tomitch, Lêda Maria Braga; Procailo, Leonilda (Letras de Hoje, 2019)
Making sense of texts from a cognitive-processing perspective involves several mental operations connecting conceptual and procedural knowledge (Gagné et al., 1993). In this regard, the reader’s ability to articulate several processes simultaneously, involving information processing and comprehension monitoring, is crucial to the construction of the mental representation of texts. Thus, this bibliographical review intends to establish theoretical relationships among reading processing, as sustained by working memory (WM) and influenced by working memory capacity (WMC), metacognition and the componential processes inherent to FL reading comprehension. The implications of the findings point to the relation of metacognition developing according to WM maturation and having an impact on reading comprehension. Therefore, as reading in a foreign language involves more complex activities and the activity per se also involves and depends upon several other variables, it is reasonable to assert that this complex activity is affected by the limitations of WM. ***Memória de trabalho, metacognição e compreensão leitora em língua estrangeira: uma revisão bibliográfica*** A construção de sentido em leitura na perspectiva do processamento cognitivo pressupõe uma gama de operações que conectam o conhecimento conceitual e o procedural (Gagné et al., 1993). Assim, a habilidade do leitor em articular vários processos simultaneamente, incluindo o processamento de informações e o monitoramento da compreensão, é crucial para a construção da representação mental de um texto. A presente revisão bibliográfica objetiva traçar discussões teóricas acerca da relação entre o processamento da leitura, sustentada pela memória de trabalho (MT) e mediada pela capacidade de memória de trabalho (CMT), metacognição e os processos componenciais inerentes à compreensão. Conclui-se que há uma relação entre a maturação da MT e o desenvolvimento da metacognição, o que influencia a compreensão leitora. Portanto, como a leitura em língua estrangeira é uma tarefa mais complexa e que também envolve e depende de outras variáveis, consideramos que essa atividade é afetada pelas limitações da MT.